Business resilience strategies for informal traders in the post-COVID-19 pandemic era in Gweru, Zimbabwe - Mabhanda, Wilson (International Journal of Financial, Accounting, and Management, 2024)
Purpose: The informal trading business is a springboard for employment and poverty reduction, even during disruptions, such as those brought about by the COVID-19 pandemic. Accordingly, this study examines the business resilience strategies adopted by informal traders to improve their livelihoods in the post-COVID-19 pandemic era in Gweru, Zimbabwe. Research methodology: An exploratory research design underpinned this study’s data collection and thematic analysis approaches. Thirteen purposively sampled participants participated in face-to-face in-depth interviews. Findings: Participants identified social networking, consignment sale agreements, business analysis, and financial capital boost as some of the business resilience strategies used by both male and female traders to improve their livelihoods in the post-COVID-19 pandemic period. Limitations: The study used a qualitative approach, whose findings could not unravel all resilience strategies adopted in the post-COVID-19 era in the whole country, as a study using a quantitative methodology could have. Accordingly, the study’s results are limited as they cannot be generalized to other cities.   Contribution:  This study incorporates informal traders’ business resilience strategies adopted in the post-COVID-19 pandemic era to sustain livelihoods and fight poverty and hunger. These strategies have not yet been used to explain the sustainability of livelihoods in post-pandemic disruptions. Novelty: Despite the COVID-19 pandemic’s disruptions, the resilience strategies adopted by informal traders enabled them to sustain their livelihoods and mitigate poverty and hunger. Consequently, the applicability of the sustainable livelihood approach has broadened in emerging economies.